Analisis Peran Koperasi Unit Desa (KUD) Lubuk Intan Dalam Membantu Pengelolaan Penjualan Kelapa Sawit Petani Pemilik Lahan Di Desa Peninjauan Kabupaten Batanghari - Bunga Puji Astuti; Anzu Elvia Zahara; Khusnul Istiqomah (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2026)
This study examines the role of the Lubuk Intan Village Unit Cooperative (KUD) in assisting in managing oil palm sales for smallholder farmers in Peninjau Village, Batanghari Regency. The background of this study is based on the suboptimal distribution of economic benefits to farmers, despite increasing sales through the cooperative. This situation indicates the need to strengthen the role of cooperatives in the harvest marketing system. This study used a qualitative approach with descriptive methods. Thirteen informants were interviewed: three administrators and ten members of the Lubuk Intan KUD in Peninjau Village, Batanghari Regency. The results indicate that the Lubuk Intan KUD plays a role in facilitating collective sales, providing price information, and creating certainty and transparency in the weighing and recording of harvests. This role has been able to improve marketing efficiency and member trust. However, its implementation still faces obstacles such as limited human resources, limited operational capital, and inadequate member participation.